A high-entropy V35Ti35Fe15Cr10Zr5 alloy with excellent high-temperature strength. (5th May 2017) - Xian, Xin; Zhong, Zhihong; Zhang, Bowen; Song, Kuijing; Chen, Chang; Wang, Shan; Cheng, Jigui; Wu, Yucheng
Abstract: Low-activation structural materials for fusion applications beyond 700 °C are desired. High-entropy alloys (HEAs) with excellent properties at elevated temperatures are suitable for use in nuclear reactors. A newly developed V35 Ti35 Fe15 Cr10 Zr5 HEA was fabricated by vacuum arc melting and the microstructure of as-cast and annealed sample was found to be composed of BCC solid solution phases. It was interesting to find that the yield strength of as-cast V35 Ti35 Fe15 Cr10 Zr5 HEA increased with increasing the temperature below 500 °C, and it was much higher than that of vanadium alloy or martensitic steel for fusion reactors in the temperature range of room temperature to 900 °C. At 700 °C, the yield strength of V35 Ti35 Fe15 Cr10 Zr5 HEA was about 500 MPa higher than that of vanadium alloy or martensitic steel, showing promise for high temperature applications. V35 Ti35 Fe15 Cr10 Zr5 alloy had a relative low ductility below 700 °C, while the alloy exhibited a good ductility above 700 °C. Graphical abstract: Highlights: A new V35 Ti35 Fe15 Cr10 Zr5 high-entropy alloy with a BCC structure was designed and fabricated. The yield strength of as-cast V35 Ti35 Fe15 Cr10 Zr5 HEA increased with increasing the temperature below 500 °C. At 700 °C, the yield strength of V35 Ti35 Fe15 Cr10 Zr5 HEA was about 500 MPa higher than that of candidate alloys. V35 Ti35 Fe15 Cr10 Zr5 alloy has a relative low ductility below 700 °C, while the alloy exhibits a good ductility above 700 °C.